Experimental study of “Tong Xia” purgative method in ameliorating lung injury in acute necrotizing pancreatitis - Xia, Qing (World J Gastroenterol, 2000)
AIM: To investigate the role of tumor necrosis factor (TNF) in lung injury during acute necrotizing pancreatitis (ANP), and the therapeutic ef fect of “Tong Xia” purgative method in minimizing the severity of lung injury. METHODS: Fourteen canines were randomly divided into 3 groups: the “Tong Xia” treatment group (n = 5) using Dachengqitang; saline control group (n = 5), and the sham operation group (n = 4). TNF activity in serum and in bronchoalveolar lavage fluid (BALF), the serum endotoxin levels were meas ured, and the severity of lung injury evaluated. RESULTS: Elevation of TNF activity was more prominent in BALF than in serum. TNF activity in serum at 6 and 12 h and in BALF was significantly decreased in the “Tong Xia” treatment group than in the saline control one (q = 21.11, q = 12.07, q = 9.03, respectively, P < 0.01) and the lung injury was significantly alleviated at 12 h as compared with that in the saline group, manifested as amelioration of the lung wet/dry weight ratio, decrease in protein concentration and neutrophils count in BALF, and improvement of pulmonary inflammatory changes. A positive correlation was demonstrated between serum TNF activity and endotoxin level. CONCLUSION: Hypersecretion of TNF is shown to be one of the majo r causes of lung injury during ANP; “Tong Xia” purgative method could allevia te the degree of lung injury mediated by TNF.